PENERAPAN PEMBELAJARAN JIGSAW DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN GEOGRAFI DI SMA NEGERI 1 REMBOKEN - Tumembouw, Anastaysa Natalia Jusia; Lobja, Xaverius Erick; Rifani, Irfan; Syafrida Selfiardy; Emanuel Estefanus Korompis; Cahyadi Nugroho (Jurnal Social Science, 2025)
The main research problem is how the use of Jigsaw learning can improve students' learning outcomes in geography subjects at SMA Negeri 1 Remboken. The research objective is to determine the use of Jigsaw learning to enhance students' learning outcomes in geography subjects at SMA Negeri 1 Remboken. The research method employed is descriptive quantitative research, with data collection techniques including observation, documentation, interviews, and tests as the main techniques. The sampling method used is purposive sampling. The research respondents are 27 students from class Xb. The research findings indicate that: 1) The results of the learning activities show that the majority of students who participated in this research demonstrated good learning activities during the learning process. 2) Most students who participated in this research showed successful participation in the learning activities, resulting in good learning outcomes. The data shows that students achieved a score of ≥ 70, with all 27 students (100% of the participants) obtaining this score. Therefore, all students are considered successful in the Jigsaw learning they participated in.